Dynamics of metal-metal bond dissociation in Pd-Pd and Ni-Ni complexes: reorganization and redistribution reactions of the metalloradicals - Bruckhoff, Tim; Kohler, Vincenz J.; Braun, Felix; Ballmann, Joachim; Gade, Lutz H. (Angewandte Chemie. International edition, 2025)
Dinuclear M(I)-M(I) complexes (M = Ni, Pd) may serve as stable reservoir forms for highly reactive mononuclear metalloradicals, which are of interest as potential catalytic species. However, their dissociation dynamics as well as the factors governing monomer stabilization remain incompletely understood. This study investigates the influence of steric bulk and residual ligand flexibility within a PNP pincer framework on the homolytic dissociation behavior of unsupported Ni(I)-Ni(I) and Pd(I)-Pd(I) dimers. Utilizing an iPrPNP pincer ligand, direct evidence of accessible reversible homolytic cleavage in such Pd(I) species has been obtained by NMR and EPR spectroscopy. A kinetic and thermodynamic analysis, coupled with DFT modeling, allowed detailed examination of the dissociation process, including geometric influences before and after cleavage on the dissociation barrier. For nickel, a T-shaped [(iPrPNP)NiI] monomer was isolated and fully characterized. Reduced steric inter-ligand repulsion for an ethyl-substituted PNP pincer yielded stable unsupported dimers for both metals. The two homodinuclear complexes underwent thermal and photochemical redistributions giving the first unbridged heterobimetallic Ni(I)-Pd(I) dimer. Thus, ligand sterics and flexibility critically tune the M-M bond strength and dissociation kinetics. Conformational adaptability lowers activation barriers for radical dissociation, while geometric relaxation stabilizes monomers, enabling controlled access to open-shell species relevant in catalytic reactions.
Gesehen am 15.01.2026